MATHEMATICAL REPRESENTATION ABILITY OF JUNIOR HIGH SCHOOL STUDENTS ON SURFACE AREA OF CUBE AND CUBOID - Nurani Mardhiyatul Gina; Nia Jusniani; Hedi Budiman (FKIP Universitas Muhammadiyah Tangerang, 2021)
Students still have difficulty in solving contextual math problems. It is because students are not used to solving problems using diverse mathematical representations. The representation can make it easier for students to solve abstract math problems. This study aims to determine and identify the types of errors and factors made by students in mathematical representation ability test questions. This study's subjects were 20 students of class VIII-H at SMPN 1 Cugenang on the Surface Area of Cube and Cuboid. The method used is qualitative. The process of collecting data is observation, written test, interview. The results showed that the level of students' mathematical representation ability based on indicators: (1) was 41% on the indicator using visual representations to solve problems and make geometrical drawings to clarify problems and facilitate resolution, (2) by 64% on indicators of problem-solving by involving mathematical expressions, (3) 61% of indicators create problem situations based on data or representations given. Furthermore, based on the analysis of students' answers in tests on a matter of mathematical representation ability, students making mistakes that are data errors, using definitions or theorems, and technicalities. Factors causing students to make mistakes are forgetfulness, lack of accuracy, learning difficulties, family environment.